2023
DOI: 10.3390/ijns10010001
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Digital PCR (ddPCR) Does Not Enhance the Sensitivity of Detection of Cytomegalovirus (CMV) DNA in Newborn Dried Blood Spots Evaluated in the Context of Newborn Congenital CMV (cCMV) Screening

Nelmary Hernandez-Alvarado,
Craig J. Bierle,
Mark R. Schleiss

Abstract: Congenital cytomegalovirus (cCMV) infection is a leading cause of sensorineural hearing loss (SNHL) and neurodevelopmental disabilities in children worldwide. Some regions in the United States and Canada have implemented universal newborn screening for cCMV, which requires molecular diagnostic technologies for identifying cCMV, such as PCR testing of newborn dried blood spots (DBS). This study aimed to evaluate the sensitivity of droplet digital PCR (ddPCR) compared to quantitative real-time PCR to detect CMV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A 2023 report describing different newborn cCMV NBS approaches makes the case that implementing universal cCMV NBS rather than a targeted screening approach improves cCMV detection, ultimately leading to better health outcomes [ 262 ]. A recent report from the Minnesota program considering droplet digital PCR (ddPCR) as a primary DBS screening tool found that ddPCR does not demonstrate any enhancement in sensitivity compared to the use of real-time PCR testing of DNA from DBSs [ 263 ].…”
Section: Resultsmentioning
confidence: 99%
“…A 2023 report describing different newborn cCMV NBS approaches makes the case that implementing universal cCMV NBS rather than a targeted screening approach improves cCMV detection, ultimately leading to better health outcomes [ 262 ]. A recent report from the Minnesota program considering droplet digital PCR (ddPCR) as a primary DBS screening tool found that ddPCR does not demonstrate any enhancement in sensitivity compared to the use of real-time PCR testing of DNA from DBSs [ 263 ].…”
Section: Resultsmentioning
confidence: 99%